OPTIMALISASI MEDIA PEMBELAJARAN BERBASIS AI DI SMK PERMAS JAYA - Ifah Rofiqoh; Fran Sayekti; Erna Fitri Komariyah; Siti Resmi; Reschiwati; Ida Musdafia Ibrahim (Universitas Bangka Belitung, 2025)
This program seeks to enhance the utilization of learning media based on artificial intelligence (AI) at SMK Permas Jaya 2, Johor, by actively engaging teachers in the process. This activity applies a participatory approach, involving teachers in planning, implementation, and evaluation. The training focuses on developing interactive and flexible learning media using AI tools, including ChatGPT, Quizlet, Kahoot, Grammarly, and Quillbot. The primary challenges include limited infrastructure, inadequate teacher skills, and data security concerns. Based on the analysis of pre-test and post-test questionnaire data, there was a notable improvement in respondents’ performance, with scores increasing from 4.39 (categorized as